Efeito da indução hormonal na qualidade espermática de Hypancistrus zebra Isbrücker & Nijssen, 1991 (Siluriformes:Locariidae) - SILVA, Adriele Lima da (2021)
Ichthyofauna conservation has been a major challenge in the face of anthropic actions resulting from the current high economic interest, which result in the overexploitation of natural resources. One of these actions was the Belo Monte Hydroelectric Power Plant, which caused the disruption of the Middle Xingu region, which has an environment rich in rapids and species diversity. Hypancistrus zebra is an endemic species of this region and is threatened with extinction due to overfishing for the aquarium market and aggravated by the implementation of Belo Monte HPP, which has disrupted the environmental quality and the course of the river. Given this, the importance of studies aimed at the conservation of species that are threatened as a result of the construction of these enterprises is notorious and one of the alternatives is ex situ reproduction. Thus, it is important to evaluate their sperm quality, being crucial to determine the success of fertilization. Such analysis is based on the qualitative study of some seminal and sperm parameters such as collected semen volume, sperm concentration, sperm motility rate, motility duration, sperm vigor, membrane integrity and sperm morphology. Therefore, if hormonal inducers are used, among them crude carp pituitary extract (EBHC), which was used in this study and was effective in the parameters of sperm vigor, increasing the quality of sperm for normal sperm morphology. decreased sperm anomalies in induced fish and seminal volume, with increased seminal fluid production allowing more effective final gamete maturation. Therefore, it was observed that EBHC allows a higher seminal quality and has no direct action on spermatogenesis.